Effect of IL-35 on the adhesion of human umbilical vein endothelial cells after sCD40L stimulation - GUO Weiwei, ZHAO Pingping, YU Lulu, LI Ming (Jichu yixue yu linchuang, 2023)
Objective To investigate the effect of interleukin (IL)-35 on vascular endothelial cell adhesion after stimulation with soluble CD40 ligand (sCD40L). Methods Thirty patients with lower extremity deep vein thrombosis in acute phase (DVT group) and 30 healthy subjects (HC group) were selected. Peripheral blood was collected, and the level of IL-35, sCD40L, VCAM-1, P-selectin and vWF in the serum was measured by ELISA. The human umbilical vein endothelial cells (HUVECs) were cultured and divided into three groups: control group, sCD40L group and IL-35 group. ELESA and Western blot were used to detect the expression of VCAM-1, ICAM-1, P-selectin and vWF. The adhesion of platelet and peripheral blood mononuclear cells to HUVECs was examined by immunofluorescence. Results Compared with control group, the level of IL-35 in serum of DVT group was significantly decreased(P＜0.05), and the levels of sCD40L, VCAM-1, ICAM-1, P-selectin and vWF were significantly increased(P＜0.05). In vitro, experiments showed that IL-35 significantly inhibited the expression of VCAM-1, ICAM-1, P-selectin and vWF in HUVECs stimulated by sCD40L(P＜0.05) and inhibited the adhesion of platelet and peripheral blood mononuclear cells to HUVECs. Conclusions IL-35 may reduce the adhesion function of HUVECs after sCD40L stimulation and inhibit thrombosis in DVT patients.